FAKTOR-FAKTOR YANG MEMPENGARUHI CORPORATE SOCIAL RESPONSIBILITY (Studi pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2014-2016) - Elpiani Br Sitepu, 14.05.62.0016; Maryono, Maryono (Students Journal of Accounting and Banking, 2017)
The purpose of this study is to influence the institutional ownership, managerial ownership, firm size, company age, profitability to corporate social responsibility in banking companies listed in Indonesia Stock Exchange (BEI) 2014-2016. The population is all companies of banking companies listed in Indonesia Stock Exchange (BEI) 2014-2016. Sampling technique using purposive sampling. The sample criteria in this study are (a) Banking companies listed on the Indonesian stock exchange in the year 2014-2016 which has published and published annual report and include the relevant CSR report in 2014-2016. (b) The Company discloses CSR or social responsibility report through its annual report. (c) The Company earns profit period of 2014-2016. Analyzer used is multiple linear regression. The results of the analysis can be concluded that: Institutional ownership has no effect on CSR. Managerial ownership positively affects CSR. Company size has no effect on CSR. The age of the company has a positive effect on CSR. Profitability has a positive effect on CSR. Keywords: Institutional Ownership, Managerial Ownership, Firm Size, Company Age, Profitability and Corporate Social Responsibility